Perbandingan Kekasaran Permukaan Resin Komposit Nanofiller pada Perendaman Saliva pH Asam - Selvy Amalia Puspitasari; Widowati Siswomiharjdo; Harsini Harsini (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2016)
Nanofiller resin composite is a material used for dental restoration which will be in oral cavity so that interacted with the saliva. Saliva pH changes influenced by several factors, including bacteria in the oral cavity, enzymes, hormones and diet. Acid saliva can cause degradation in the composite, this degradation affects the surface roughness of resin composite. The purpose of this study is to compare surface roughness of nanofiller resins composite for 7 and 10 days of immersion in acid saliva.The samples used in this study were cylindrical mould dimension of diameter 5mm x 2mm, then polymerized with a visible light curing unit for 20s. Specimens immersed in acid artificial saliva (pH ± 4) for 7 and 10 days(4 specimens each group)and then stored in incubator at the temperature of 37ºC. The instrument used to measure surface roughness of resin composite was Surface Roughness Measuring Instrument (Surfcom 120A) that expressed in units of µm.Data were analyzedand the result obtainedwas p = 0.263 (p> 0.05), which mean there were no significant differences in the mean roughness of nanofillerresins compositesurface that were immersed in acidic pH for 7 and 10 days. The conclusion of this study was thatthe surface roughness of nanofiller resins composite immersed in acid saliva for 10 days is not rougher than which immersed for 7days.